Character Educational Values of Sikambang Dance in Traditional Wedding Ceremonies of Sibolga Community - Lubis, Anisah Sari; Hanum OK, Azizah; Arsyad, Junaidi (Journal of Educational Sciences, 2025)
Sikambang dance is a cultural heritage in the traditional wedding ceremony of the Sibolga community, which contains noble values such as cooperation, responsibility, politeness, respect for customs, and love for local culture. However, the existence of this dance is increasingly being eroded by technological advances and cultural shifts, making it less known to the younger generation. This study aims to identify and analyze the character education values embedded in the Sikambang Dance. The study employs an ethnographic method with a field-based approach through direct observation, interviews, and active participation within the Sibolga community. The findings reveal that the Sikambang Dance is not merely a form of entertainment but also a tool for character development among the younger generation based on local wisdom. This research is expected to serve as a reference in efforts to preserve culture and strengthen character education rooted in local values.